2022
DOI: 10.3389/fmars.2022.948836
|View full text |Cite
|
Sign up to set email alerts
|

A system of marine animal bioconstructions in the mesophotic zone along the Southeastern Italian coast

Abstract: A widespread and diversified mesophotic system of carbonate bioconstructions along the Southern Adriatic and Ionian Italian coasts is described, providing new data on the distribution, structure and associated megabenthic assemblages of mesophotic Mediterranean bioconstructions. The bioconstructions were detected at six different sites off the coasts of Apulia, in presence of marked morphological escarpments, developing on a basal substrate consisting of meso-Cenozoic carbonate rocks. Two biogenic structure ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…The Albanian coralligenous showed some peculiarities, since three sponge species recorded during the present study (Petrobiona massiliana, Hexadella racovitzai, and Merlia normani) were not included in the Apulian coralligenous biodiversity checklist [61], although H. racovitzai has been recently described within Apulian mesophotic biogenic reefs [7][8][9].…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…The Albanian coralligenous showed some peculiarities, since three sponge species recorded during the present study (Petrobiona massiliana, Hexadella racovitzai, and Merlia normani) were not included in the Apulian coralligenous biodiversity checklist [61], although H. racovitzai has been recently described within Apulian mesophotic biogenic reefs [7][8][9].…”
Section: Discussionmentioning
confidence: 82%
“…The associated faunal component plays an important role in structuring these bioconstructions. When light conditions are not suitable to support algal communities, animals can take over the role of the main builders, giving rise to mesophotic reefs built by scleractinians or oysters [7][8][9]. There is usually a clear spatial separation between substrates dominated by algae or animals, thus creating a complex mosaic of facies in which few dominant species alternate even at a small scale.…”
Section: Of 19mentioning
confidence: 99%
“…This dataset includes previously published information [12][13][14] complemented by more recent data presented here for the first time, with an overall sampling period ranging from 2017 to 2023. The six study sites were selected based on preliminary geophysical investigations and ROV images resulting from a previous research project (BIOMAP) aimed at studying bioconstructions along the Apulian coast.…”
Section: Methodsmentioning
confidence: 99%
“…The dataset includes records gathered from 6 sites along the Apulian coast (Southeastern Italy), where our research [12][13][14] revealed the occurrence of large bioconstructions. The sites, located from north to south, are as follows: the Tremiti Islands (TRM); Monopoli (MON); Capitolo (CAP); San Foca (SFC); Otranto (OTR); and Santa Maria di Leuca (SML) (Figure 1).…”
Section: Geographic Coveragementioning
confidence: 99%
See 1 more Smart Citation